78.7k views
5 votes
If p(x) = x^2 – 1 and q(x) = 5(x-1), which expression is equivalent to (p – q)(x)?


User Gries
by
6.1k points

2 Answers

6 votes

Answer:

x² - 5x + 4

Explanation:

note (p - q)(x) = p(x) - q(x) , thus

p(x) - q(x)

=x² - 1 - 5(x - 1) ← distribute parenthesis

= x² - 1 - 5x + 5 ← collect like terms

= x² - 5x + 4

User Marius Waldal
by
5.1k points
0 votes

Answer:

x^2 - 5x - 6

User Scymex
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.